Dietary habits and physical activity: Results from cluster analysis and market basket analysis. Issue 2 (June 2018) - Liew, Hui-Peng
Background: The prevalence of obesity remains a major public health concern and there has been a significant increase in childhood obesity in the USA. Aim: This study seeks to uncover the major patterns of dietary habits in relation to physical activity, together with students' opinions about the quality of food in the school's cafeteria and vending machines. Methods: The empirical work of this study is based on the 2011 Healthy School Program (HSP) Evaluation. HSP assesses the demographic characteristics as well as the dietary habits and exercise patterns of a representative sample of elementary, middle, and high school students in the USA. Results: Findings suggest that students assigned to different clusters have different eating habits, exercise patterns, weight status, weight management, and opinions about the quality of food in the school's cafeteria and vending machines. There is great variation in dietary profiles and lifestyle behaviors among students who identified themselves as either overweight or unsure about their weight status. Conclusions: Findings from this study may inform future interventions regarding how to promote student's healthy food choices when they are still in school. Health promotion initiatives should specifically target students with persistently unhealthier dietary profiles.